If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -21 = -12 + 9x Reorder the terms: -21 + 6x = -12 + 9x Solving -21 + 6x = -12 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -21 + 6x + -9x = -12 + 9x + -9x Combine like terms: 6x + -9x = -3x -21 + -3x = -12 + 9x + -9x Combine like terms: 9x + -9x = 0 -21 + -3x = -12 + 0 -21 + -3x = -12 Add '21' to each side of the equation. -21 + 21 + -3x = -12 + 21 Combine like terms: -21 + 21 = 0 0 + -3x = -12 + 21 -3x = -12 + 21 Combine like terms: -12 + 21 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| P+7/4=37/8 | | 1.5x5/8 | | 0.22y-2.5=0.12y+1-0.6y | | 2y^3+3y^2-50y-75= | | x+x^2=2 | | (4y-8)/(3y)=6 | | 1/2/2 | | (-8c^2+4c+6)-(6c^2+7c-3)= | | -3n+7=-2 | | 9x^6-24x^4/3x^3 | | 8(2x+6)+13= | | 2(5x-31)+2x=72 | | 8/4+39/8=p | | (4y-8)/3y=6 | | 3x^2+2-16=0 | | 2(5x-31)(2w)=72 | | 2y^3+y^2-50y-75= | | -4x^2+(-7x)+(-4)+3x^2+8x+(-4)= | | -36x=3(6y-6) | | 4y-8/3y=6 | | 2(5x-31)+2x= | | X-8/4=7 | | 3x+2xy-5+x+3xy+10= | | 6/x=3/7 | | 480-8y=8 | | -2=w/-5 | | 6+w=12 | | 2(5x-31*x)= | | 9e-2=5e+26 | | 22x+26=48 | | y=0(8)+8 | | 120=(x+1)(x+20) |